Peningkatan Konsiderasi Pelanggan Dengan Optimalisasi Pemasaran Digital Berbasis Periklanan Digital : Studi Kasus Sutarman Dental Care - Dhruvatara Dax Andhara; Muhammad Odivio Octhursa Youhan (Jurnal Publikasi Ilmu Manajemen, 2024)
The purpose of this final project is to enhance the effectiveness of digital advertising implementation strategies, create structured guidelines and measurement systems for advertising, and produce landing pages and ad content to support digital advertising at Sutarman Dental Care. The approach used to write the final project report is through in-depth interviews with Sutarman Dental Care partners. This project was carried out from November 28, 2023, to June 18, 2024. The results of the project show that optimizing digital advertising at Sutarman Dental Care, supported by the implementation of Meta Ads, Google Ads, and the creation of landing pages, can increase the level of customer consideration at Sutarman Dental Care. These findings are in line with customer consideration theory, where potential customers seek more information about services before making a purchase decision. These potential customers are called prospects. Informative and relevant ad content and landing pages have proven to be effective in attracting and educating prospects, thereby driving brand engagement and considering Sutarman Dental Care as a primary choice.